Penerapan Strategi Pemasaran Produk Keripik Sanjai Sukarasa Terhadap Kepuasan Konsumen Menggunakan Metode STP dan 4P (Studi Kasus – Bisnis Sanjaiku) - Sakti, Salas Maulidan Rahma; Hidayat, Hidayat; Negoro, Yanuar Pandu (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The application of the Sanjai Sukarasa chips marketing strategy to customer satisfaction using the STP and 4P methods. This study aims to analyze marketing strategies, customer satisfaction, and provide recommendations to improve the marketing of Sanjai Sukarasa chips products. The research method applied is a quantitative approach by collecting data through filling out questionnaires. The results showed that the company uses a differentiation marketing strategy with a focus on product quality and promotion. In addition, consumer satisfaction with Sanjai Sukarasa chips products is quite high, but there are still several things that need to be improved. The recommendations given include improving product quality, increasing promotion, and developing new products.